Antwerpen in vogelvlucht - Huysmans, Camille; Sabbe, Maurits; Mielants, Flor; Zielens, Lode; Prims, Floris (Antwerpen : De Sikkel, 1937)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: Antwerpen